Investigation of Exhaust Emissions of Vehicles with the Spark Ignition Engine within Emission Control. (2017) - Sarkan, Branislav; Stopka, Ondrej; Gnap, Jozef; Caban, Jacek
Abstract: The level of exhaust gases production of road vehicles is mainly influenced by legislation that determines the maximum values of individual gases elements. However, inter alia, vehicles composition in given region or country is very important aspect in the context of exhaust gases production in normal operation. The paper is focused on the data analysis of the emission controls results in selected workstation during years 2005 to 2014. In the paper, analysis regarding the relation of level of the exhaust emissions selected elements of different emission systems according to year of vehicle production is processed.